Soaked Water of Rice Straw Ash and Ziziphus mauritiana Leaf Extract as Disinfectant: A Microbiological Assessment - Yulia, Yulia; Amaliyah, Nurul (Yayasan Ahmad Mansyur Nasirah, 2025)
Commercial dishwashing liquids contain chemicals that are extremely toxic to humans and the environment, hence alternative dishwashing using natural compounds is urgent. The purpose of this study was to evaluate the effect of a combination formula of rice straw ash and Ziziphus mauritiana leaf extract (JEBI) in reducing germs colonies per food equipment. This experimental study has a pre-post-test design with a control group. The variations of the JEBI combination used are 1:1, 1:2, 1:3, 2:1, and 3:1. Another treatment is using a commercial dishwasher brand